2020
DOI: 10.17221/49/2020-rae
|View full text |Cite
|
Sign up to set email alerts
|

Field evaluation of a vibrating dual bent-share cultivator

Abstract: In this research, the suitability of a vibrating dual bent-share cultivator was studied. Therefore, an eccentric pin-slider mechanism was designed to vibrate the two shanks laterally, using a tractor power take-off. The present study investigates the field performance of the vibrating dual bent-share cultivator with three different vibration frequencies (0, 0.88, and 2 Hz) in a clay loam soil at two working depths (100 and 200 mm) and having a water content of a 0.7 or 0.9 plastic limit. The lowest values of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Increasing the tillage depth from 10 to 20 cm increased the MWD by 24.9%. Other studies have also shown that the MWD value increased with an increasing tillage depth (Yassen et al 1992;Solhjou et al 2001;Esehaghbeygi et al 2020). Increasing the tillage depth increased the MWD value due to the higher compaction in the deeper soil layers.…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…Increasing the tillage depth from 10 to 20 cm increased the MWD by 24.9%. Other studies have also shown that the MWD value increased with an increasing tillage depth (Yassen et al 1992;Solhjou et al 2001;Esehaghbeygi et al 2020). Increasing the tillage depth increased the MWD value due to the higher compaction in the deeper soil layers.…”
Section: Resultsmentioning
confidence: 80%
“…The draught force of the bent leg tillage implement at an operating depth of 20 cm increased by 35.1% compared to the draught force at an operating depth of 10 cm. Other studies have shown that the draught force increased with an increasing tillage depth (Godwin and O'Dogherty 2007;Naderloo et al 2009;Moeenifar et al 2014;Esehaghbeygi et al 2020). Increasing the operating depth increased the draught force, which was due to increasing the soil compaction at deeper soil layer and, as a result, the friction force between the soil and blade increases.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations